Analysis of Processing Rare Earth Elements from Monazite as Tin by Product Mineral - Budi Nur Rochmadi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
This paper focuses on industry attractiveness of processing monazite into Rare Earth Elements (REE). The analysis is using Porter’s Five Forces (PFF). PFF is a framework for the industry analysis and business strategy development developed by Michael E. Porter. In addition, we took four of the six Politics Economic Social Technology Environment and Legal (PESTEL) analyzes to see if there is an impact of these four factors in deriving the conclusion. With combined factors of increasing demand on China’s domestic and the soaring world consumption of growing-demand products have impacted to shortfall of supply. The total demand for selected REE in 2040 is projected to increase around 300% compared to 2010. With current supply unless new Rare Earth Oxides (REO) production is developed, the shortage will become even wider. Based on PFF analysis the Rare Earth (RE) Processing Industry is currently attractive. It indicates that the existing players are enjoying healthy margin. Three factors are showing weak, they are: threat of entrance, rivalry amongst existing player and threat of substitution. The bargaining Power of supplier and bargaining power of buyers are both classified as moderate. In general, the industry outlook is promising as it is predicted the demand still outstrip the supply for the next 5-10 years.